The Communication And Governance Challenges In African Smes - Amr Sukkar (International Journal of Social Communication, 2020)
In the last few years, there has been a rise in corporate governance around the world. On the African region, it is clear there is an increasing number of national corporate governance reports that have been produced. This report analyzes these national codes of corporate governance in Africa. Providing a background to the corporate governance developments. In Africa, there have been good indicators of a move from conventional approaches to governance reform toward a new convention that uses African localities and everyday norms as the starting point for transformation